Technical ability in the women's 100m hurdles - Bedini, R. (New Studies in Athletics, 2016)
Many commentators feel that because of the relatively low height of the hurdles (84cm) the women's 100m hurdles is not as technically demanding as the men's 110m hurdles (hurdle height: 106.7cm) and therefore it is dominated by sprinters rather than athletes with the very specific ability to hurdle. However, analysis of the difference between the personal best 100m flat time and personal best 100m hurdles time of the world's top hurdles performers shows that technical ability can make a significant difference and that there is more to success in the women's event than pure sprinting speed. Therefore, coaches should give the same emphasis to technique in the training of women hurdlers as they do for men hurdlers. The author, a scientist and successful coach, presents statistics illustrating the importance of technical ability in the women's 100m hurdles and then describes the key elements of hurdling technique with the help of photos of the world's top performers. He concludes with practical advice for coaches comprising five sets of training objectives and drills that can be used with both male and female hurdlers.